PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN MELALUI KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Produk Ayam Broiler Di PT. Mitra Peternakan Unggas Unit Pandeglang) - Yeni Firmawati (JUBISMA, 2022)
ABSTRACT Broiler Chicken Farms have very good prospects for development, both on a large and small scale. Broilers are the only poultry that have an important role because they produce meat that provides the availability of animal protein, the manure can be used as organic fertilizer and the feathers can be used as industrial materials. One of the companies engaged in the field, especially Broiler Chicken is PT.Mitra Poultry Farm. PT. Mitra Poultry Farm, which is located in the Cigadung Indah Complex Block C/21 RT/RW 03/05, Cigadung Village, Karang Tanjung District, Pandeglang Regency, Banten. To be able to compete in this broiler farming business, the company must improve product quality and good service quality in order to create customer purchasing decisions for broiler chickens optimally so that it will have an impact on customer satisfaction of broiler chicken products at PT Mitra Peternakan Poultry Unit Pandeglang. Based on this, this research raises the title "INFLUENCE OF PRODUCT QUALITY AND PAYMENT QUALITY ON CUSTOMER SATISFACTION THROUGH PURCHASE DECISIONS AS INTERVENING VARIABLES". Based on the research that has been carried out, the results obtained are that product quality has a positive and significant effect on customer satisfaction through purchasing decisions for broiler chicken products from PT, Mitra Poultry Farming Unit Pandeglang. This means that product quality and service quality indirectly affect customer satisfaction through the decision to purchase broiler chicken products from PT. Mitra Pandeglang Poultry Farm. Keywords: Product Quality, Service Quality, Customer Satisfaction, Customer Purchase Decisions